The Reproduction Rate of Peptide Transporter PEPT-1 Deficient C. elegans Is Dependent on Dietary Glutamate Supply - Spanier, Britta; Wallwitz, Jacqueline; Zapoglou, Despoina; Idrissou, Bio Maria Ghéo; Fischer, Christine; Troll, Martina; Petzold, Katrin; Daniel, Hannelore (Frontiers in Molecular Biosciences, 2018)
Intestinal absorption of dietary amino acids is mediated via two routes. Free amino acids released by hydrolysis of dietary proteins are taken up by a multitude of amino acid transporters while di- and tripeptides released are taken up by the peptide transporter PEPT-1. Loss of PEPT-1 impairs growth, post-embryonic development and reproduction in Caenorhabditis elegans, and supplementation with a mixture of all L-amino acids only partially rescues fertility. In the present study, we demonstrate that dietary L-glutamate is the responsible amino acid that can increase fertility in hermaphrodite pept-1 worms. This effect was associated with a significantly higher uptake of glutamate/aspartate in pept-1 than in wildtype C. elegans. Furthermore, we found that the intestinal transporter proteins SNF-5 of the solute carrier SLC6 family of nutrient amino acid transporters (NAT) and AAT-6 of the SLC7 family as the light subunit of a heteromeric amino acid transporter (HAT) play a key role in glutamate homeostasis in pept-1 C. elegans. Genes encoding these transporters are highly expressed and upon silencing a 95% reduced fertility (snf-5) and sterility (aat-6) was observed. A subsequent L-glutamate supplementation failed to rescue these phenotypes. Dietary glutamate supplementation did neither influence the feeding frequency, nor did it improve mating efficiency of pept-1 males. Most strikingly, pept-1 were more prone to habituation to repeated gentle touch stimuli than wildtype C. elegans, and dietary glutamate supply was sufficient to alter this behavioral output by restoring the mechanosensory response to wildtype levels. Taken together, our data demonstrate a key role of L-glutamate in amino acid homeostasis in C. elegans lacking the peptide transporter in the intestine and demonstrate its distinct role in reproduction and for neural circuits mediating touch sensitivity.